2014
DOI: 10.1093/ser/mwu019
|View full text |Cite
|
Sign up to set email alerts
|

Explaining corporate short-termism: self-reinforcing processes and biases among investors, the media and corporate managers

Abstract: Based on the related literature in economics, organizational sociology and the sociology of finance, this article constructs a novel conceptual explanation for corporate short-termism, that is, the tendency of corporate managers to sacrifice long-term investments to improve short-term earnings (STEs). We theorize about how such corporate short-termism emerges, at least partly, from systemic, self-reinforcing processes across various communities of actors including investors, the media and managers themselves. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 106 publications
0
10
0
Order By: Relevance
“…The systematic and self‐reinforcing processes are something that Aspara et al . () and Whittle and Mueller () have been investigating recently in relation to investors, the media and the banks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The systematic and self‐reinforcing processes are something that Aspara et al . () and Whittle and Mueller () have been investigating recently in relation to investors, the media and the banks.…”
Section: Discussionmentioning
confidence: 99%
“…Aspara et al . () theorized about self‐reinforcing processes and biases within organizations when they investigated the causes for corporate short‐termism. Most recently, Whittle and Mueller () have used similar ideas when they examined the testimonies of leaders of British banks during a UK public inquiry into the financial crisis.…”
Section: Practical Reasoning Vocabularies Of Motive and Organizationmentioning
confidence: 99%
“…Firstly, Crotty (2005) suggested that the increase in nonfinancial corporations' financial investments (which also take the form of buying or expanding financial subsidiaries) was caused by pressure from shareholders to raise current profitability and thus a focus on shorter planning horizons. The short-termism of non-financial corporations reflects the tendency to sacrifice long-term investments in order to improve short-term profits (Hein 2012;Aspara et al, 2014;and Hein and Dodig, 2015). Samuel (2000) defines this focus by managers on short-term profits at the expense of long-term expansion as "managerial myopia".…”
Section: Investmentmentioning
confidence: 99%
“…This short-termism mirrors a tendency among investors to sacrifice long-term investment projects in order to increase short-term profits (Aspara et al, 2014). According to Samuel (2000), this focus on short-term profits instead of long-term expansion reflects a certain "managerial myopia".…”
Section: Lower Retention Ratios (More Financial Payments)mentioning
confidence: 99%